Educational Innovation Policy for Improving Digital Literacy Capabilities in Higher Education - Muh Tahir Malik; Nurhikmah H; Muhammad Azmi; Kurniati Kurniati (Madrasah Tsanawiyah DDI Cilellang, 2023)
The era of disruption innovation forces higher education institutions to innovate and have good technological literacy skills. This study aims to examine educational innovation policies in higher education institutions and their implications for the technological literacy capabilities of their academic community. This literature research uses journals and books as data sources. Data collection used documentation techniques and was then analyzed using content analysis techniques. The results of the study found that ICT-based educational innovation policies in higher education institutions resulted in several programs, such as (1) ICT-based selection processes, (2) management of electronic scientific journals, (3) online libraries, (4) higher education academic systems, and (5) use of the internet in learning. These policies have implications for increasing the digital literacy capabilities of the academic community, which regards ICT as an integral part of their daily activities and influences their behavior and culture of life. The implication of this research is that the government must provide a complete and easily accessible ICT-based educational infrastructure. It should not be difficult for educational institutions and the public to finance their digital access.